LONTAR TUTUR CANDRABHERAWA PERSPEKTIF PENDIDIKAN AGAMA HINDU - Wulandari, Ida Ayu Gde (Institut Hindu Dharma Negeri Denpasar, 2019)
The literary works belonging to the traditional literary written in ancient times by using lontar. This tradition is still done until now aiming to bequeath literary treasure. One of the literary works that has educational values of Hinduism is Lontar Tutur Candrabhérawa. It tells about two king, namely Yudhistira, who ruled in the kingdom of Astina Pura and the Candrabhérawa who ruled in the kingdom of Dewantara. Both king have two different understanding, namely the concept of Karma Sanyasa and Yoga Sanyasa. It tells us that life does not separate from karma and yoga. The goals in this study is that the literary Lontar Tutur Candrabhérawa with its intrinsic structure which consist of a theme, characters, plot, incident, background, and mandate. Review from the function of education, based on the classification of Bloom?s taxonomy, containing three functions of education, namely cognitive, affective and psychomotor. Meanwhile, when viewed from educational values of Hinduism, it contains religious, patriotism, environmental care, respect, and the right appointment. With these findings can be expected to create human characters that are religious, ethical, and social spirit in religious life.